Persepsi dan Partisipasi Anak Petani dalam Usahatani Padi Keluarga: Analisis Model Rasch - Heryanto, Mahra Arari; Pardian, Pandi; Julia, Anna (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
The youth's perception of the agricultural sector determines their participation in agriculture. This negative view of the sector, which is the mainstay of rural development, has resulted in the general aging of farmers in Indonesia. Farmers are portrayed as unsuccessful, dirty, and full of risks, so that many households whose parents do not want their children to work as farmers. Youth perceptions and participation, especially those in families farming, are interesting to assess. The objective of this study is to assess the perceptions and involvement (participation) of farmer's children in rice farming operations conducted by their parents, whether it is positive or negative. The results found that young farmers' children had a fairly positive perception of their family's rice farming, but this was not followed by their participation. The factor of unfavorable grain prices during the harvest is the biggest concern for their family's economic life. Therefore, they are most reluctant to be fully involved in the family farm.